Kedudukan dan Perlindungan Hukum Advokat dalam Menjalankan Profesi pada Tahap Penyidikan Perspektif Undang-Undang Nomor 20 Tahun 2025 tentang Kitab Undang-Undang Hukum Acara Pidana - Annisa Dwi Ramadhanti; Zahratunnisa Zahratunnisa; M. Ahsani Taqwim; Musleh Harry (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The position of advocates during the investigation stage constitutes an important issue in the criminal justice system due to the persistent imbalance between investigators and suspects, which may result in violations of suspects’ rights. This study aims to analyze the position and legal protection of advocates under Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code from the perspective of due process of law. This research employs normative legal research using statutory and conceptual approaches. The findings indicate that the new Criminal Procedure Code strengthens the position of advocates by regulating the right to provide legal assistance from the early stage of investigation, access to Investigation Reports (Berita Acara Pemeriksaan), confidential communication with clients and enhanced professional immunity. Normatively, these provisions provide a stronger legal basis for protecting suspects’ rights and upholding the principle of due process of law. However, this study is limited to examining the normative legal framework, while the effectiveness of its implementation requires further empirical assessment following the enactment of the law.